PENGARUH PERATAAN LABA, UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO, DAN RETURN ON ASSETS TERHADAP REAKSI PASAR PERUSAHAAN PERTAMBANGAN TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Marco Marco; Muhammad Khafid (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The purpose of this study is to to find empirical evidence and to determine the effect of income smoothing, firm size, debt to equity ratio, return on assets on market reactions. The population used in this study is mining sector companies listed on the Indonesia Stock Exchange in the period 2017 to 2019. The sampling technique in this study uses an purposive sampling with a 35 unit of analysis that are processed. The research data collection method uses the documentation method. The research data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Hypothesis testing in this research using multiple linear regression analysis tools The results of this research showed that the retun on assets variable has a significant positive effect on market reaction, the income smoothing variable does not have an influence on market reaction, the firm size does not have an influence on market reaction, and the debt to equity ratio does not have an influence on market reaction. The conclusion from the results of this study that companies that increasingly have a high rate of return on assets ratio will attract investors to invest